Рассказы - Чехов Антон Павлович (Пушкинская библиотека, 2000)
Экземпляры: аб. (2001) / Инвентарный номер: 42949 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Ч-56 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)1